2007
DOI: 10.1111/j.1463-1318.2007.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase of serum C‐reactive protein is an early indicator of subsequent symptomatic anastomotic leakage after anterior resection

Abstract: The level of the anastomosis was at a median 5 cm (3-12 cm) above the anal verge. There was no 30-day mortality. Nine (27.2%) of the 33 patients developed a symptomatic anastomotic leakage which was diagnosed at a median of 8 days (range 4-14) postoperatively. The serum CRP was increased in patients who leaked from postoperative day 2 onwards (P = 0.004 on day 2; P < 0.001 on day 3-8). The WBC was decreased in preoperatively irradiated patients on days 1-5 (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
79
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 24 publications
9
79
1
2
Order By: Relevance
“…22,28 Both studies reported persistently increased CRP values after POD 2-4 in patients later diagnosed with an anastomotic leak. Matthiessen et al 28 prospectively studied several risk factors for anastomotic leaks in 33 patients, and Welsch et al 22 compared 48 patients with anastomotic leaks to 48 matched patients with an uncomplicated postoperative course from a large database. However, in both studies, the median CRP values were used as cut-offs with their corresponding diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 98%
“…22,28 Both studies reported persistently increased CRP values after POD 2-4 in patients later diagnosed with an anastomotic leak. Matthiessen et al 28 prospectively studied several risk factors for anastomotic leaks in 33 patients, and Welsch et al 22 compared 48 patients with anastomotic leaks to 48 matched patients with an uncomplicated postoperative course from a large database. However, in both studies, the median CRP values were used as cut-offs with their corresponding diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 98%
“…We have shown that a decrease in inflam- We are aware that the anastomotic leakage rate is relatively high compared with other series [23,31,32] . However, our results represent consecutive patients including our first experience.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, several studies have only described the preoperative and intraoperative risk factors for AL. High CRP levels on POD 3 or persistently elevated CRP levels are considered to be early predictors of AL after colorectal surgery [10][11][12][13][14] . However, one paper reported no differences in CRP levels between the AL and non-AL groups after total colectomy for familial adenomatous polyposis [16] .…”
Section: Discussionmentioning
confidence: 99%
“…A sustained high fever and contaminated discharge from the intra-abdominal drain are the clinical signs of AL after LAR. In addition, an increased serum C-reactive protein (CRP) level might be an early indicator of AL after LAR [10][11][12][13][14] . The early predictors of AL are very useful in clinical practice.…”
Section: Introductionmentioning
confidence: 99%